Anti-Diabetes Activity of Ethanolic Extract of Cassia Alata Leaves on Hyperglycemia Model Mice - Sasmita, Sasmita; Hujjatusnaini, Noor; Nirmalasari, Ridha (Universitas Sultan Ageng Tirtayasa, 2024)
Indonesia has a geographically rich region with medicinal plants, including Cassia alata. The utilization of this medicinal plant still needs to be improved, including documentation of its use as medicine. Information about the extract of Cassia alata leaves as an anti-diabetes therapy can be conveyed to future generations. This research aims to prove the potential of Cassia alata leaf extract as a hyperglycemia therapy material through a mouse model. The research design uses a pretest-posttest group design. The antidiabetic activity of Cassia alata leaf extract in vivo is determined by the indicator of reducing blood sugar levels in mice with hyperglycemia, supported by quantitative testing of secondary metabolite compounds. The experimental animals used 24 male Balb/c mice induced with 0.75 mg/kgBb alloxan. Measure blood sugar levels in mice with hyperglycemia after treatment with Cassia alata leaf extract at concentrations of 25%, 50%, 75%, and 100%, and a positive control using metformin—data analysis using one-way ANOVA correlation analysis. Cassia alata leaf extract is proven to contain alkaloids, flavonoids, tannins, triterpenoids, and saponins. The antidiabetic activity is evidenced by an effective reduction in blood sugar levels at a concentration of 50%, where the average data for the reduction in blood sugar levels in hyperglycemic mice is 93 mg/dL. The 50% concentration is proven to have the best antidiabetic effect, supported by a more significant reduction in blood sugar levels than the positive control. The findings of this research are expected to serve as the basis for further development of innovative hyperglycemia therapy products.